AWARENESS AND ATTITUDE OF RURAL ADOLESCENT GIRLS REGARDING REPRODUCTIVE HEALTH ISSUES IN NORTHERN INDIA - Agarwal, Monika; Singh, J V; Srivastava, A K (Indian Journal of Community Health, 2009)
Background: Since adolescent girls comprise a major reproductive age group, their role is critical in determining the India's future population goal. This apart, evidence ofchange in sexual behavior and growing spread of HIV infection, has generatedfresh reproductive health concerns, which need to be accountedfor by policy makers to develop appropriate family life educational strategies. Objectives: To assess the level of knowledge ofoubertal changes, reproductive tract infections and HIV/AIDS among adolescents. To assess the attitude of adolescent girls regarding age at marriage, age at first birth, small family concept. To identify the preferred source of information by adolescents on reproductive health. Study design: cross- sectional study Sampling Technique: thirty cluster methodology Study setting: Rural areas of Luc know Participants: 455 unmarried adolescent girls of (10-19 years) age. Statistical A nalysis: Chi square test and Fischer exact test Result: Three fourth of the girls were aware of at least one pubertal change. In spite of being aware that RTI is a curable disease, only 8.5% of the girls having RTI sought treatmentfor it. About 80% ofadolescent girls had heard of HIV/AIDS. 47.7% ofadolescents were unaware that it is incurable. Heterosexual relation was cited by most (73.2%) ofthe girls as mode oftransmission of HIV. Sex with partner only and use ofcondom as a preventive measure was identified by 52.6% and 39.2% girls respectively. Early marriage and early child bearing (<2I years) was preferred by 10.7% and 33.6% of girls respectively. Family size oftwo or less was preferred by 69.2%> Irrespective ofany age group, majority of the girls preferred afamily member to get information on reproductive health problems